(untitled) (Bangladesh Journal of Medical Biochemistry, 2013)
This cross-sectional study was carried out in 80 serologically diagnosed cases of acute viral hepatitis to assess and compare the serum hepatic enzymes & plasma proteins between four different types (A,B,C,E), 20 in each group. Hepatitis E, hepatitis B and hepatitis C were more prevalent in males than that in females. The study showed that geometric mean of S.AST of all the four types differed significantly (F= 274.94, p<0.001). Geometric mean of S.ALT, S.AST and S.ALP in cases of HCV were significantly lower than others (p<0.001). Geometric mean of S.ALT & S.AST in cases of HEV were significantly increased than others (p<0.001). But the geometric mean of S.ALP of HBV was significantly higher than others (p<0.001). On the other hand though S.ALP of HAV and HEV was lower than HBV but significantly higher than HCV (p<0.001). The mean±SD of serum albumin of HCV was decreased significantly in contrast to those of HAV and HBV (p<0.001). A:G ratio of HCV was also significantly lower than other three (p<0.001). It was revealed through the study that hepatic enzymes were most affected in cases of HEV but least affected in cases of HCV. DOI: http://dx.doi.org/10.3329/bjmb.v3i1.13803 Bangladesh J Med Biochem 2010; 3(1): 19-22